Aspects of Quality Management of Islamic Education Nahdlatul Wathan West Nusa Tenggara - Mahmudi Abdillah; Afif Anshori; An Andari (Journal La Sociale, 2024)
Nahdlatul Wathan has contributed greatly to all the people of West Nusa Tenggara. Related to the field of education and its role in helping the government educate the people and nation. Where nowadays, in fact, the needs and aspirations of the community are getting bigger in the field of education, it seems that this is one of the driving forces for Nahdlatul Wathan to try to improve and develop itself in education management. As for its growth and development, it seems that pesantren, madrasas, or schools were established both in the context of upholding the Islamic religion and nationalism. In achieving quality aspects of education, of course, requires careful planning, for example identifying priority programs and goals to be achieved, organizing according to their respective areas of expertise to the maximum, effectively and efficiently. It is also necessary to manage the improvement of educator standards such as conducting supervision in order to produce quality education as well. So that Nahdlatul Wathan has aspects of education management that have Islamic values, practices and culture that can be respected, internalized and practiced in all aspects of education quality management of Nahdlatul Wathan West Nusa Tenggara.